Mathematics 17: College Algebra and trigonometry

Sample exercises: Exponential and Logarithmic equations
General Direction: Use black or blue ballpen. Show neat and clean solutions to obtain full points.
I.

Solve for the value of 𝑥. Discard any values that would not fit into the equation.
1.
2.
3.

23𝑥+1 = 4𝑥+5
2
25𝑥 +𝑥 = 5𝑥+1
2
82𝑥 = 45𝑥+2

4.

9𝑥−1 −

1 4𝑥−1
3 𝑥
−2

3𝑥

=0

5.
6.

9 − 27
=0
7𝑥 𝑥+4 − 7 = 0

7.

32𝑥+1 =

8.

3 9𝑥
(𝑥 2 )

1

2 −4𝑥

2−𝑥

16

= 81−𝑥

9.

8
27𝑥

21.
22.
23.
24.
25.
26.
27.
28.
29.
30.
31.

log 3 2𝑥 2 − 15𝑥 = 3
log 3 4𝑥 − 1 + log 3 𝑥 + 1 = 2
log 2 𝑥 3 + 1 − 2 log 2 𝑥 2 − 1 = 0
log 𝑥 + 2 − log 𝑥 = log 12
log 4 𝑥 2 − 3𝑥 − log 4 5 − 4𝑥 = −1
log 2 𝑥 + 3 + log 2 𝑥 − 1 = 1
log 2 11 − 𝑥 − 3 = log 2 𝑥 + 1
4−𝑥
log 3 𝑥 + 7 − log 3
=2 𝑥

log 2 2𝑥 − 3 + log 2 𝑥 − 1 = 3 + log 2 (1 + 3𝑥)
log 3 2𝑥 − 1 − log 3 (5𝑥 + 2) = log 3 𝑥 − 2 − 2
log 𝑥 + log 𝑥 − 200 − log 4 = 5 − log 5

=

1
4

10.
11.
12.
13.
14.
15.
16.
17.
18.
19.
20.

32𝑥+1 = 53𝑥−1
42𝑥−1 − 5𝑥−1 = 0 𝑒
2𝑥 + 4 = 5𝑒 𝑥
3𝑒 2𝑥 − 4 + 𝑒 𝑥 = 0 𝑒
2𝑥 − 5𝑒 𝑥 − 6 = 0 𝑒
2𝑥 + 𝑒 = 𝑒 𝑥+1 + 𝑒 𝑥
2𝑒 2𝑥 − 𝑒 𝑥 + 𝑒 −𝑥 = 2
4𝑥+1 − 6 2𝑥 + 2 = 0
25 52𝑥 + 24 5𝑥 − 1 = 0
32𝑥 + 3𝑥+1 − 18 = 0
32𝑥+1 + 2 3𝑥 = 1

32.
33.
34.
35.
36.
37.
38.
39.
40.

ln 𝑒 3𝑥 + 27 − ln 4 = ln(𝑒 2𝑥 − 3𝑒 𝑥 + 9)
ln 𝑥 2 − ln(𝑥 2 ) = 8
3 ln 𝑥 2 − 4 ln(𝑥 2 ) + 4 = 0
log 4 10 = log 4𝑥 𝑥
+ ln 5 = ln(7 − 2𝑒 2𝑥 ) 𝑥
= ln 𝑒 2𝑥 − 3 − ln 2
ln 2𝑒 2𝑥−3 = (ln 5) + 𝑥
1
2
3
99 𝑥
= (log ) + (log ) + (log ) + ⋯ + (log )
2
3
4
100 𝑥
= (log 2 3) ∗ (log 3 4) ∗ (log 4 5) ∗ ⋯ ∗ log 99 100

Mathematics 17: College Algebra and trigonometry
Sample exercises: Exponential and Logarithmic equations
General Direction: Use black or blue ballpen. Show neat and clean solutions to obtain full points.
I.

Solve for the value of 𝑥. Discard any values that would not fit into the equation.

1.
2.
3.

23𝑥+1 = 4𝑥+5
2
25𝑥 +𝑥 = 5𝑥+1
2
82𝑥 = 45𝑥+2

4.

9𝑥−1 −

1 4𝑥−1
3 𝑥
−2

3𝑥

=0

5.
6.

9 − 27
=0
7𝑥 𝑥+4 − 7 = 0

7.

32𝑥+1 =

8.

3 9𝑥

9.
21.
22.
23.
24.
25.
26.
27.
28.
29.
30.
31.

2
8(𝑥 )

27𝑥

2 −4𝑥

=

1

2−𝑥

16

= 81−𝑥

1
4

log 3 2𝑥 2 − 15𝑥 = 3
log 3 4𝑥 − 1 + log 3 𝑥 + 1 = 2
log 2 𝑥 3 + 1 − 2 log 2 𝑥 2 − 1 = 0
log 𝑥 + 2 − log 𝑥 = log 12
log 4 𝑥 2 − 3𝑥 − log 4 5 − 4𝑥 = −1
log 2 𝑥 + 3 + log 2 𝑥 − 1 = 1
log 2 11 − 𝑥 − 3 = log 2 𝑥 + 1
4−𝑥
log 3 𝑥 + 7 − log 3
=2 𝑥

log 2 2𝑥 − 3 + log 2 𝑥 − 1 = 3 + log 2 (1 + 3𝑥)
log 3 2𝑥 − 1 − log 3 (5𝑥 + 2) = log 3 𝑥 − 2 − 2
log 𝑥 + log 𝑥 − 200 − log 4 = 5 − log 5

10.
11.
12.
13.
14.
15.
16.
17.
18.
19.
20.

32𝑥+1 = 53𝑥−1
42𝑥−1 − 5𝑥−1 = 0 𝑒
2𝑥 + 4 = 5𝑒 𝑥
3𝑒 2𝑥 − 4 + 𝑒 𝑥 = 0 𝑒
2𝑥 − 5𝑒 𝑥 − 6 = 0 𝑒
2𝑥 + 𝑒 = 𝑒 𝑥+1 + 𝑒 𝑥
2𝑒 2𝑥 − 𝑒 𝑥 + 𝑒 −𝑥 = 2
4𝑥+1 − 6 2𝑥 + 2 = 0
25 52𝑥 + 24 5𝑥 − 1 = 0
32𝑥 + 3𝑥+1 − 18 = 0
32𝑥+1 + 2 3𝑥 = 1

32.
33.
34.
35.
36.
37.
38.
39.
40.

ln 𝑒 3𝑥 + 27 − ln 4 = ln(𝑒 2𝑥 − 3𝑒 𝑥 + 9)
ln 𝑥 2 − ln(𝑥 2 ) = 8
3 ln 𝑥 2 − 4 ln(𝑥 2 ) + 4 = 0
log 4 10 = log 4𝑥 𝑥
+ ln 5 = ln(7 − 2𝑒 2𝑥 ) 𝑥
= ln 𝑒 2𝑥 − 3 − ln 2
ln 2𝑒 2𝑥−3 = (ln 5) + 𝑥
1
2
3
99 𝑥
= (log ) + (log ) + (log ) + ⋯ + (log )
2
3
4
100 𝑥
= (log 2 3) ∗ (log 3 4) ∗ (log 4 5) ∗ ⋯ ∗ log 99 100

Sign up to vote on this title
UsefulNot useful